Sosialisasi Pentingnya Minat Membaca Untuk Generasi Muda Panti Asuhan Imanuel di Kota Palangka Raya - Novalisae, Novalisae; I Putu Putrawiyanta; Ferdinandus, Ferdinandus; Noveriady, Noveriady; Lisa Virgiyanti; Hepryandi L. Dj. Usup; Yos David Inso; Neny Sukmawatie; Nuansa Mare Apui Ganang; Yossa Yonathan; Yusias Andri (Fakultas Teknik Universitas Palangka Raya, 2024)
Reading is an activity that stimulates the brain through written symbols that convey information and reasoning. According to the UNESCO report, Indonesian people's interest in reading is very low, namely 0,001%, which means one in 1.000 Indonesians read diligently. To increase the young generation's passion for reading, a reading culture must be instilled from childhood. This must be achieved by making the culture of reading fun and easily accepted by the younger generation, because of the challenges of increasingly rapid development and various advances in information technology, the culture of reading children's books is increasingly being eroded. Involving children directly is one way to encourage their interest in reading. To encourage children at the Immanuel Orphanage to be more motivated to learn, this service activity aims to provide quality teaching, both materially and morally. This is based on the fact that some children lack interest in learning, especially in reading. This service activity motivates children and shows the fun side of reading to gain broad knowledge. The activity methods used are socialization and motivating learning, especially in fostering interest in reading in the younger generation